2021
DOI: 10.1016/j.arbres.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Disseminated Tuberculosis in a Child with Crohn's Disease After Treatment with Azathioprine, Adalimumab and Ustekinumab

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…[27][28][29][30][31][32] To the best of our knowledge, only 1 other case of TB in a child treated with ustekinumab has been reported to date. Renoux et al 33 described an 11-year-old girl who developed a disseminated M. tuberculosis infection shortly after starting ustekinumab for CD. Similar to our case, the patient had previously undergone multiple immunomodulatory therapies (azathioprine, adalimumab and steroids), had received BCG vaccination in childhood, and had tested negative for Mantoux reaction (with indeterminate IGRAs) before starting immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32] To the best of our knowledge, only 1 other case of TB in a child treated with ustekinumab has been reported to date. Renoux et al 33 described an 11-year-old girl who developed a disseminated M. tuberculosis infection shortly after starting ustekinumab for CD. Similar to our case, the patient had previously undergone multiple immunomodulatory therapies (azathioprine, adalimumab and steroids), had received BCG vaccination in childhood, and had tested negative for Mantoux reaction (with indeterminate IGRAs) before starting immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Ustekinumab was started without a new chest X-ray or a repeat interferon gamma release assays test because the child was switched from another biologic. [40] Also, another case described drug-induced lung disease after starting Ustekinumab; the child complained of shortness of breath, chest pain, and cough. [41] Adult clinical trials are expanding the therapeutic options for IBD patients, but the time lag between adult and pediatric drug approval results in significant off-label use due to a lack of knowledge about optimal pediatric dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the roles of the IL-12/IL-23 pathway in protecting the host from pathogens, however, ustekinumab may result in unintended downstream consequences such as the development of new infections or reactivation of underlying infections ( Trinchieri, 2003 ; Langrish et al, 2004 ; Tato and Cua, 2008 ; Shen and Chen, 2018 ). Since ustekinumab approval, HBVr, TB, and AMI have been reported occasionally in patients treated with it ( Sánchez-Moya and Daudén, 2012 ; Tsai et al, 2013 ; Errichetti and Piccirillo, 2014 ; Lynch et al, 2017 ; Shim et al, 2018 ; Renoux et al, 2020 ; Akiyama et al, 2021 ; Tominaga et al, 2021 ). To the best of our knowledge, no previous study has investigated the relationships between these infections and ustekinumab exposure by using a pharmacovigilance database.…”
Section: Discussionmentioning
confidence: 99%
“…Although cases of TB and AMI have been occasionally reported with ustekinumab, ( Sánchez-Moya and Daudén, 2012 ; Tsai et al, 2013 ; Errichetti and Piccirillo, 2014 ; Lynch et al, 2017 ; Shim et al, 2018 ; Renoux et al, 2020 ; Tominaga et al, 2021 ), increased risks to date have not been observed in clinical trials. In fact, ustekinumab is generally safer in terms of infectious complications than TNF inhibitors, the most commonly used biologics in autoimmune diseases ( Kalb et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation